Peningkatkan Motivasi Belajar Siswa SMPN 3 Karang Ploso Malang Menggunakan Metode Johari Windows - Pranoto, Setyo; Akhzalini, Hana Athia (Jurnal Pengabdian Masyarakat: Pemberdayaan, Inovasi dan Perubahan, 2024)
When the harvest arrives, students of SMPN 3 Karangploso prefer to work harvesting and/or selling the harvest rather than going to school. Even in the partner's experience, when the school is in the middle of UAS or UTS, students are willing to leave UTS and/or UAS for the sake of the harvest season. Provide information about jobs and the benefits that can be obtained when students want to continue their higher education. Motivational seminar on the importance of managing your career using Johari windows method.As a result of the service that has been carried out, researchers have obtained results of increasing student learning motivation. This is proven by the increase in motivation as measured by the student learning motivation instrument. The results increased student learning motivation on average by 20%. The career motivational lecture method and also the Johari Windows technique are able to increase the learning motivation of female students at SMPN 3 Karangploso. This research can have a positive impact in terms of learning motivation, so that they study harder and can achieve their desired career dreams in the future.ABSTRAKKetika panen tiba, siswa SMPN 3 Karangploso lebih memilih untuk ikut bekerja memanen dan atau berjualan hasil panen daripada bersekolah. Bahkan dalam pengalaman mitra, ketika sekolah sedang UAS atau UTS, siswa rela untuk meninggalkan UTS dan atau UAS demi musim panen itu. Memberikan informasi pekerjaan-pekerjaan dan manfaat-manfaat yang bisa di dapat ketika siswa-siswa mau melanjutkan pendidikan yang lebih tinggi. Seminar motivasi tentang pentingnya menata karir menggunakan metode Johari windows. Hasil dari pengabdian yang telah dilakukan, peneliti mendapatkan hasil peningkatan motivasi belajar siswa. Dibuktikan dengan angka kenaikan motivasi yang di ukur dengan instrumen motivasi belajar siswa. Hasil kenaikan motivasi belajar siswa rata-rata sebanyak 20%. Metode ceramah motivasi karir dan juga teknik Johari windows mampu menaikkan motivasi belajar siswa siswi SMPN 3 karangploso. Penelitian ini dapat memberikan suatu dampak positif dalam hal motivasi belajar sehingga mereka lebih giat belajar lagi dan dapat meraih Impian karir yang diinginkan di masa depan.